Monitoring climate change and child health: The case for putting children in all policies. (18th November 2021) - Romanello, Marina; McGushin, Alice; MacGuire, Frances A S; Sly, Peter D; Jennings, Bethany; Requejo, Jennifer; Costello, Anthony
Abstract : Climate change is threatening the health of current and future generations of children. The most recent evidence from the Lancet Countdown: Tracking Progress on Health and Climate Change finds declining trends in yield potential of major crops, rising heatwave exposures, and increasing climate suitability for the transmission of infectious diseases, putting at risk the health and wellbeing of children around the world. However, if children are considered at the core of planning and implementation, the policy responses to climate change could yield enormous benefits for the health and wellbeing of children throughout their lives. Child health professionals have a role to play in ensuring this, with the beneficiaries of their involvement ranging from the individual child to the global community. The newly established Children in All Policies 2030 initiative will work with the Lancet Countdown to provide the evidence on the climate change responses necessary to protect and promote the health of children.